Assessment of the Functional Status of the Small Intestine in Patients with Non-Alcoholic Fatty Liver Disease - Ya. M. Vakhrushev; A. P. Lukashevich (Архивъ внутренней медицины, 2020)
The aim. A comprehensive study of the functional state of the small intestine and the study of the relationship of its disorders with the development of non-alcoholic fatty liver disease.Materials and methods. 86 patients with non-alcoholic fatty liver disease at the stage of steatosis and steatohepatitis were examined according to the results of ultrasound examination of the liver using the SONIX OP apparatus (Canada) and the FibroMax test of BioPredictiv company (Paris, France). Patients underwent a blood glucose test using an Huma Star 600 analyzer (Germany) and insulin using an enzyme-linked immunosorbent assay. The HOMA-IR insulin resistance index was calculated. In order to determine abnormal digestive disorders in the small intestine, a stress test was performed with soluble starch, membrane digestion with sucrose, absorption with glucose. IDBs were evaluated using a hydrogen breath test on a LactofN2 apparatus from the AMA firm (St. Petersburg). To assess colonic microflora, stool was sown for dysbiosis.Results. According to clinical data, in patients with non-alcoholic fatty liver disease, damage to the small intestine occurs in a non-manifest form. However, in the study of the functional state of the small intestine in patients, a significant decrease in cavity and membrane digestion, increased absorption are detected. In patients with non-alcoholic fatty liver disease, an increase in blood insulin was observed compared with the control group (16,64±0,78 μIU/ml versus 10,46±0,56 μI/ml, p=0,000002). The HOMA-IR insulin resistance index was also increased in patients compared with the control group (2,84±0,11 versus 2,05±0,07, p=0,00003). Excessive bacterial growth was diagnosed in 62 (72%) of patients with non-alcoholic fatty liver disease, while with liver steatosis — in 33 (55%), with steatohepatitis 1 degree of activity — in 11 (61,1%), with steatohepatitis 2 degrees — in 6 (66,7%), with steatohepatitis 3 degrees — in 2 (100%) of patients. According to the results of stool stool, dysbiosis was detected in 56 (65,1%) of patients with non-alcoholic fatty liver disease. A correlation analysis revealed negative relationships between the severity of excessive bacterial growth and digestive digestion, between the severity of excessive bacterial growth and membrane digestion, and a positive relationship between the severity of excessive bacterial growth and absorption.Conclusion. Non-alcoholic fatty liver disease is accompanied by disorders of the digestive and resorptive functions of the small intestine, and the development of dysbiosis. These disorders are often subclinical in nature and can be identified and evaluated after special studies.